Field gamma-ray spectrometer GS256: measurements stability - MOJZEŠ, Andrej (Contributions to Geophysics and Geodesy, 2009)
The stability of in situ readings of the portable gamma-ray spectrometer GS256 during the ﬁeld season of 2006 was studied. The instrument is an impulse detector of gamma rays based on NaI(Tl) 311 × 311 scintillation unit and 256-channel spectral analyzer which allows simultaneous assessment of up to 8 radioisotopes in rocks. It is commonly used in surface geophysical survey for the measurement of natural 40 K, 238 U and 232 Th but also artiﬁcial 137 Cs quantities. The statistical evaluation is given of both repeated measurements - in the laboratory and at several ﬁeld control points in diﬀerent survey areas. The variability of values shows both the instrument stability and also the relative inﬂuence of some meteorological factors, mainly rainfalls.The analysis shows an acceptable level of instrument measurements stability, the necessity to avoid measurement under unfavourable meteorological conditions and to keep detailed ﬁeld book information about time, position and work conditions.